User Experience Analysis of the Old and New SIAKAD at the Faculty of Tarbiyah, UIN Ar-Raniry with a UI/UX Approach - Susanti, Widia; Yasa, Gufran Ibnu (Jurnal Teknologi Informatika dan Komputer, 2025)
The world of education is currently developing very rapidly. This rapid development is in line with the development of technology and information. The diversity of information technology requires improvements in the quality and service mechanisms in the field of education to be more effective. The development of information technology requires higher education institutions to continue to innovate in academic service systems. One form of this innovation is the implementation of the Academic Information System (SIAKAD) which is able to integrate various academic services digitally. This study aims to analyze the user experience of two versions of SIAKAD used at the Faculty of Tarbiyah UIN Ar-Raniry, namely the old SIAKAD and the new SIAKAD (Sevima), using the User Interface (UI) and User Experience (UX) approaches. This study uses a quantitative descriptive method with a questionnaire instrument based on the Technology Acceptance Model (TAM), which includes perceptions of usefulness, ease of use, and user satisfaction. A total of 32 student respondents were involved in completing the questionnaire. The results showed that the new SIAKAD (Sevima) received a satisfaction level of 76%, included in the "Satisfied" category on the Likert scale. These findings show that a friendlier UI and more optimal UX in the new SIAKAD have a positive impact on user comfort and effectiveness in carrying out academic activities. This research recommends the development of more responsive features that meet user needs, such as adding the option to download active student certificates independently through the system.